Investigation of some bioactive Thai medicinal plants - Chulabhorn Mahidol (2018)
It has been estimated that plants are the most important source of medicine for more than 80% of the world's population. Medicinal plants are a vital source of medication in developing countries. Despite the wealth of human experience and folklore concerning the medicinal uses of plants, proper scientific investigation has only been applied to a small fraction of the world's plants. This is a cause of grave concern as plant species continue to disappear. A rapid response to this situation is urgently needed to prevent the disappearance of the plant species and the ethnopharmacological knowledge that accompanies them. In this review, recent work on the investigation of selected bioactive Thai medicinal plants is presented. Their biological activities against infectious diseases including antimalarial and anti-HIV, are highlighted, as well as their anticancer, antiulcer and anti-inflammatory properties. The chemical transformations of some selected compounds are discussed. © 2003 Kluwer Academic Publishers.